Patient Satisfaction and Associated Factors among Patients of Dental Profession Students, Indonesia: A Cross Sectional Study - Fakhrul Fitrianto; Diki Bima Prasetio; Hayyu Failasufa; Retno Kusniati (Indonesian Journal of Global Health Research, 2025)
Patient satisfaction regarding oral health services is defined as the difference between the patient's view of the services they receive and their expectations of these services. Communication is one of the factors that contribute to increasing the level of patient satisfaction. Meanwhile, communication problems are often a patient complaint as 35%-40% of patients are not satisfied when consulting with a doctor. Analyzing the relationship between patient satisfaction and the provision of communication, information, and education carried out by dental profession students at the Dental and Oral Hospital of Muhammadiyah University, Semarang. Method: This type of research is observational with cross sectional design. The population is 101 consisting of dental professional student patients. The sampling technique uses accidental sampling. The independent variables are the provision of IEC, age, gender, and level of professional students and the dependent variable is patient satisfaction. The questionnaire to measure patient satisfaction and the provision of IEC was taken from previous studies and has been proofread. Validity testing was conducted using expert judgment, with heterotrait-monotrait (HTMT) ratios below 0.9, and the reliability test using Cronbach's alpha yielded a result of 0.7. Ethical approval has been obtained and data collection involves informed consent and questionnaire interviews. Data analysis was carried out with univariate and bivariate using rank spearman correlation and Chi-square. There is a relationship between the provision of IEC with patient satisfaction (p = 0.000). there is no relationship between age (p = 0.840), gender (p = 1.000) and the level of professional students (0.260) with patient satisfaction. the results of patient satisfaction at RSGM Unimus assessed by patients have very satisfactory results. Maintaining and improving patient satisfaction is needed by RSGM to achieve maximum service quality. There is a relationship between the provision of communication, information, and education with patient satisfaction.